Exploring University Student’s Academic Anxiety in Online Learning from the Fear of Missing Out (FoMO) Perspective - Herliana, Mavalda; Marsofiyati, Marsofiyati; Utari, Eka Dewi (Asian Journal of Applied Education (AJAE), 2025)
This study aims to explore the emotional experiences of undergraduate students in online learning, focusing on academic anxiety and the Fear of Missing Out (FoMO) phenomenon. Through a descriptive qualitative approach, this study involved nine students from various universities in Indonesia who had different experiences of online learning. In-depth interviews revealed key challenges such as decreased motivation, lack of interaction, and psychological pressure due to academic demands and social comparison on digital platforms. The findings show that students not only face academic burdens, but also internalized pressures related to digital presence and peer comparison achievements. Despite this, most informants demonstrated emotional resilience through adaptive strategies such as time management, self-reflection, and emotion regulation. The novelty in this study lies in its holistic perspective, which combines academic, emotional and social aspects to understand students' experiences during digital learning. Unlike previous research that tends to separate these factors, this study highlights the interconnectedness of these elements and encourages educational institutions to consider emotional sustainability as an important component in designing online learning systems.